Molecular epidemiology of campylobacteriosis and evolution of Campylobacter jejuni ST-474 in New Zealand : a thesis presented in partial fullfilment [sic] of the requirements for the degree of Doctor of Philosophy at Massey University, Institute of Veterinary, Animal and Biomedical Sciences, Massey University, Palmerston North, New Zealand - Mohan, Vathsala (Massey University, 2011)
Population genetics and phylogenetics have the potential to provide enormous insights into the epidemiology and ecology of disease causing pathogens. Molecular datasets are the basis to infer population structure, gene flow (between host populations and between different geographical locations) and to predict the evolutionary dynamics of pathogens. Campylobacter colonisation in food producing animals has been extensively studied and the population structure and host association of C. jejuni, the most commonly reported gastro-enteric pathogen, has also been well defined. In contrast, host-pathogen relationships and the population structure of C. jejuni in urban wild birds and pets have not been well defined on a wide range of spatial and/or temporal scales. A greater understanding of these details should allow disease control authorities to track the transmission of pathogens from one host species to another, identify the origin of pathogens and to better understand environmental factors influencing underlying molecular mechanisms. In the first study in this thesis the presence of C. jejuni in mallard ducks and starlings within five playgrounds in Palmerston North, New Zealand was studied. The prevalence of Campylobacter and C. jejuni in both species showed a bimodal seasonal pattern. The population structure and population differentiation of C. jejuni in these species were examined using multilocus sequence typing (MLST). Rarefaction analyses showed that the C. jejuni populations within mallard ducks were more diverse than starlings, particularly during the winter. Pairwise fixation indices showed that the population of C. jejuni in ducks was significantly different from that of starlings and that it differed over time. Conspicuous host association was evident with clonal complexes of C. jejuni such as ST-1034, ST-692 and ST-1332 specific to ducks and ST-177 and ST-682 specific to starlings. In addition, a larger proportion of C. jejuni genotypes that could not be assigned a clonal complex were found in both ducks and starlings, particularly during the winter. In the second study, C. jejuni from domestic pets (dogs and cats) were characterised using MLST and by typing the cell surface antigens, porA and flaA. The ST-45 complex, a clonal complex predominantly reported in human campylobacteriosis cases, was found to be the predominant clone present in both species. These findings shed some light on the contribution of pets as a putative source of human campylobacteriosis cases in New Zealand. In the third study, the ST-474 C. jejuni genotype, considered to be the endemic strain in New Zealand, was isolated from human cases and poultry carcasses from the Manawatu region from 2005 to 2009. Seven samples of ST-474 were sequenced and a subset of 50 full length genes were studied. These analyses demonstrated molecular differences between full length genes that were identical in the region used for MLST. Further, alleles characteristic of the ST-474 genome within the investigated metabolic housekeeping genes (n = 25) were identified. Our findings were that ST-474 genome is genetically distinct from other C. jejuni reference genomes with respect to certain alleles. In addition, MLST alleles were found to be robust predictors of the most recent common ancestors of a genome. The fourth study investigated the genetic stability and vulnerability of the informational genes to various evolutionary forces within the seven ST- 474 genomes. Twenty five genes comprised of nucleotide metabolism, repair and ribosomal functions were investigated showing a high level of genetic diversity in the DNA repair as well as nucleotide metabolic genes such as gidA, ogt, recJ, ssb, uvrA, uvrB and xseA. In contrast, the ribosomal genes were stable and identical across the seven genomes. The insertion of selenocysteine in three of the 25 genes indicates the presence of horizontal gene transfer within the ST-474 genomes. It is hypothesised that the genetic uniqueness of ST-474 may have arisen due to the geographic isolation of New Zealand, its poultry industry and an absence of exchange of sequence types which might typically occur through international trade of fresh poultry meat. Collectively, the studies presented in this thesis provide a better understanding of the dynamism of C. jejuni as a species and ST-474’s adaptational capacity and evolutionary potential (within the investigated set of genes) in response to changing intracellular and extracellular environments. This thesis has introduced the idea of using individual full length gene analysis, demonstrating the molecular differences between genes that contained identical alleles at the MLST loci. The research approaches implemented in this thesis can be readily applied to any pathogenic bacteria, particularly foodborne and emerging pathogens such as E. coli and Salmonella. This, in turn should provide new opportunities for bacterial drug targets and vaccine candidates.
Keywords: Campylobacter jejuni; Molecular aspects; Molecular epidemiology; Campylobacter infections; New Zealand; Epidemiology